Proses Posttraumatic Growth pada Perempuan Dewasa Awal dengan Melihat Sifat Kepribadian dan Ruminasi Kedukaan - Putri, Evita Pamela; Hidajat, Lidia Laksana (Suksma: Jurnal Psikologi Universitas Sanata Dharma, 2023)
The Covid-19 pandemic and the changing circumstances that followed can disrupt grieving process and lead to maladaptive grief. Emerging adults who experience parental death are vulnerable since loss at this age tends to be unanticipated and potentially disrupt the development process. Nevertheless, a loss can produce positive changes called posttraumatic growth (PTG) as a result of the struggle facing adversity. This study examines the process of PTG by looking at personality traits and grief rumination and using a qualitative approach. Three emerging adults aged 25-26 years who experienced parental death during the pandemic were involved and selected using purposive sampling. Data was collected mainly by semi-structured interviews and analyzed by thematic analysis. Results indicated that PTG is a complex process, unique to each individual, and involving substantial cognitive processing. The dynamics of personality traits and grief rumination also play a role. Positive and reinforcing personality traits, such as conscientiousness, openness to experience, extraversion, and agreeableness, can help participants overcome grief and experience positive changes after loss. Meanwhile, neuroticism was found to hinder PTG. Furthermore, meaning in grief rumination plays the most prominent role to determine the process of PTG in the participants of this study. The ability to see a positive meaning from the loss helps to achieve PTG and conversely the tendency to think of the negative meaning can inhibit PTG. Thus, intervention given to emerging adults who have lost their parents should target grief rumination, especially aspect of meaning, and take into account differences in individual personality traits.